2007
DOI: 10.1158/1078-0432.ccr-07-1036
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Prognostic Nomogram for Men with Hormone-Refractory Metastatic Prostate Cancer: A TAX327 Study Analysis

Abstract: Purpose: To develop a prognostic model and nomogram using baseline clinical variables to predict death among men with metastatic hormone-refractory prostate cancer (HRPC). Experimental Design: TAX327 was a clinical trial that randomized 1,006 men with metastatic HRPC to receive every three week or weekly docetaxel or mitoxantrone, each with prednisone. We developed a multivariate Cox model and nomogram to predict survival at 1, 2, and 5 years. Results: Ten independent prognostic factors other than treatment gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
272
2
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 344 publications
(298 citation statements)
references
References 37 publications
19
272
2
5
Order By: Relevance
“…Recently, an analysis of a TAX327 cohort indicated that baseline PSADT was an independent predictor of survival, demonstrating that patients with a short PASDT (less than 55 days) had a lower chance of survival compared with patients who had a more indolent PSADT. 10 As mentioned above, our study also demonstrated that a rapid increase in the serum PSA level, namely, a short PSADT, is independently associated with a negative survival outcome. The median OSs for patients with PSADT ,46.3 days and those with PSADT o46.3 days were 14.0 months and 23.0 months, respectively (P50.001).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Recently, an analysis of a TAX327 cohort indicated that baseline PSADT was an independent predictor of survival, demonstrating that patients with a short PASDT (less than 55 days) had a lower chance of survival compared with patients who had a more indolent PSADT. 10 As mentioned above, our study also demonstrated that a rapid increase in the serum PSA level, namely, a short PSADT, is independently associated with a negative survival outcome. The median OSs for patients with PSADT ,46.3 days and those with PSADT o46.3 days were 14.0 months and 23.0 months, respectively (P50.001).…”
Section: Discussionsupporting
confidence: 80%
“…There are several reports available regarding the prognostic impact of PSADT for prostate cancer patients. 10,16,17 D'Amico et al 16 suggested that the PSADT should be confirmed as a useful surrogate marker for survival and as a tool to identify patients at risk of progression after radical prostatectomy or radiotherapy. Teeter et al 17 reported that in an older, racially diverse cohort, a short PSADT (less than 9 months) on recurrence after radical prostatectomy was associated with worse all-cause mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic nomogram was first developed by Armstrong et al to predict the survival rate among men with mCRPC after chemotherapy. 15 In addition to traditional prognostic markers, this multivariate prognostic model, based on the TAX327 trial, included some novel prognostic variables, such as pre-treatment PSA kinetics, the presence of pain, number of metastatic sites and the type of disease progression at baseline. In their study, the area under the curve was 0.69 for predicting the 1-, 2-and 5-year survival.…”
Section: Discussionmentioning
confidence: 99%
“…When adding clinical features, the model showed an area under the curve of 0.69 in the development cohort. 15 The challenge of nomograms is that they are frequently based on a retrospective analysis with a certain group of patients. Before these encouraging findings can be used in routine clinical practice, they must be validated in an external unrelated cohort.…”
Section: Introductionmentioning
confidence: 99%